Macroecotoxicology: challenges and opportunities to study broad-scale biodiversity patterns under the effect of microplastics contamination - Moulatlet, Gabriel M. (2023)
Despite several advances in the field of ecotoxicology, the implication of the effects of xenobiotics on species’ macroecological responses can only be inferred. Almost a decade ago Beketov & Liess (2012) [1] called for the integration of the fields of ecotoxicology and macroecology as a way to unravel the global impacts of environmental pollution on biodiversity patterns. In this mini-review, we dig into the literature from the last three years on the responses of marine invertebrates to microplastics (MPs) as a study case to assess the challenges and opportunities for the emerging field of macroecotoxicology. We discuss 1) to what extent the recent studies on the marine invertebrate species responses to MPs have applied the principles of macroecotoxicology and 2) how macroecotoxicology can be used to evaluate the shifts in expected species diversity patterns, and so to define priorities for investigating global effects of MPs on marine invertebrate species.